2020
DOI: 10.3390/nano10040765
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Lippia citriodora Microwave Extract into Total-Green Biogelatin-Phospholipid Vesicles to Improve Its Antioxidant Activity

Abstract: Phytochemicals from Lippia citriodora leaves were extracted by applying an innovative technology based on the use of microwaves, which represents an alternative method to extract bioactive substances. The obtained extract was incorporated into phospholipid vesicles in order to promote the antioxidant effect of the bioactive molecules present in L. citriodora extract. The extract was analyzed by High Performance Liquid Chromatography coupled to Time-Of-Flight mass spectrometer by electrospray (HPLC-ESI-TOF-MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…These concentrations were expressed in mg analyte/g extract. The range of total phenolic content obtained under different PLE conditions was similar to those described in the literature for plant phenolic extracts obtained by advanced extraction techniques [34,35]. As it can be seen, PLE 1 condition (40 °C, 15% EtOH, 20 min) was the best combination in the extraction of hydroxybenzoic acid family.…”
Section: Quantification Of Polar Compounds In C Grandis Seed Ple Extsupporting
confidence: 81%
See 1 more Smart Citation
“…These concentrations were expressed in mg analyte/g extract. The range of total phenolic content obtained under different PLE conditions was similar to those described in the literature for plant phenolic extracts obtained by advanced extraction techniques [34,35]. As it can be seen, PLE 1 condition (40 °C, 15% EtOH, 20 min) was the best combination in the extraction of hydroxybenzoic acid family.…”
Section: Quantification Of Polar Compounds In C Grandis Seed Ple Extsupporting
confidence: 81%
“…Finally, the subclass of proanthocyanidins included Peaks 8,12,13,14,21,23,29,31,32,33,34,35, 37 and 39. Peaks 8 and 12 were detected in all extraction conditions.…”
Section: Flavonoidsmentioning
confidence: 99%
“…The treatment with hydrogen peroxide only, caused a mortality of 30% of cells (viability ~70%), suggesting a toxic effect of this stressing agent (Leyva-Jiménez et al, 2020). The treatment with the extract in dispersion did not reduce the damages as the cell viability remained unchanged (~70%, p>0.05 versus the viability of stressed and untreated cells).…”
Section: Evaluation Of the Biological Activity Of The Extract Loaded ...mentioning
confidence: 92%
“…For example, Leyva‐Jimenez et al . (2020) added citrate lipid extracted from lemon leaves to glycerol‐modified liposomes. Studies have shown that the modified liposomes had stronger antioxidant properties than the aqueous solution of the extract.…”
Section: The Purpose and Methods Of Liposome Modificationmentioning
confidence: 99%